Valuing changes in environmental attributes with discrete choice models: an application to sportfishing in the east coast of U.S.A. - McConnell, Kenneth (Estudios de Economía, 2016)
Consumer decisions regarding quality or attribute differentiated goods, involve discrete or qualitative choice regarding an exhaustive set of mutually exclusive alternatives determined by preferences over the attributes that characterize the alternatives, not over the alternatives themselves. From the standpoint of the researcher, in any choice occasion, some of the determinants of preferences will be unobserved, like taste variations and/or perceptions of quality for example, giving rise to a random utility model of choice. This type of models is well suited to study choices among environmental goods that are differentiated by their quality attributes, and allows us to investigate the value of changes in these attributes. The present paper has three purposes. First, we want to show the potential of discrete choice models to study consumers behavioural changes when economic or environmental policies affect the attributes of natural resources. Second, we show how to use the results of such models to measure the welfare effects associated to there policies in order to conduct benefit-cost analysis. Third, we show a way to incorporate demand changes, caused by the policies, in order to obtain complete welfare measures.